Pengaruh Kontrol Otoritas dan Strategi Bisnis Terhadap Sistem Informasi Akuntansi Manajemen (SIAM) Pada Perusahaan Farmasi Di Palembang - Fenny Marietza; Cardova Gloria Artha Siahaan (UNIB Press, 2016)
This research aims to examine influenceof control authorities and business strategy towards informationmanagement accounting systems (SI AM) on the company pharmacy in Palembang. The population used in the studyin the i that is p erusahaan f armasi in Palembang. Samples in research use respon en Pharmaceutical companyManager in Palembang that understands the systems account information tansi was man ajemen (SI AM). Dataresearch results processed by downloading will double the ber linear esi regr yan g showed positive and significanteffect of controling formal management accounting information system (SIAM). Control authority in formalinfluential positif and significantly limited management accounting information system (SIAM). Influential businessstrategy positively and significantly to management accounting information system (SIAM).Keywords: Control Authority, Business Strategy, Management Accounting Information System.